2018
DOI: 10.5194/bg-2018-166
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon Stocks and Accumulation Rates in Salt Marshes of the Pacific Coast of Canada

Abstract: Tidal salt marshes are known to accumulate "blue carbon" at high rates relative to their surface area and have been put forth as a potential means for enhanced CO2 sequestration. However, estimates of salt marsh carbon accumulation rates are based on a limited number of marshes globally and the estimation of carbon accumulation rates require detailed dating to provide 5 accurate estimates. We address one data gap along the Pacific Coast of Canada by estimating carbon stocks in 34 sediment cores and estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…However, some of the studies included in those global reviews used shorter-term accretion methods such as feldspar, which overestimate long-term accretion. Other studies along the west coast of North America report natural marsh rates more comparable to ours (all using 210 Pb dating), including an estimated 79 g C m -2 yr -1 from San Francisco Bay [29], 77 g C m -2 yr -1 from Oregon [25], and 115 g C m -2 yr -1 from British Columbia, Canada [30]. Within the Puget Sound, Crooks et al [12] reported 110 g C m -2 yr -1 from a natural marsh in the Snohomish estuary and Drexler et al [13] reported a 50-year rate of 118 g C m -2 yr -1 from the Nisqually River estuary, both similar to our Stillaguamish average of 123 g C m -2 yr -1 .…”
Section: Carbon Stocks and Accumulation Ratessupporting
confidence: 82%
“…However, some of the studies included in those global reviews used shorter-term accretion methods such as feldspar, which overestimate long-term accretion. Other studies along the west coast of North America report natural marsh rates more comparable to ours (all using 210 Pb dating), including an estimated 79 g C m -2 yr -1 from San Francisco Bay [29], 77 g C m -2 yr -1 from Oregon [25], and 115 g C m -2 yr -1 from British Columbia, Canada [30]. Within the Puget Sound, Crooks et al [12] reported 110 g C m -2 yr -1 from a natural marsh in the Snohomish estuary and Drexler et al [13] reported a 50-year rate of 118 g C m -2 yr -1 from the Nisqually River estuary, both similar to our Stillaguamish average of 123 g C m -2 yr -1 .…”
Section: Carbon Stocks and Accumulation Ratessupporting
confidence: 82%
“…We do not use the same background value to estimate supported 210Pb in all 5 cores, as the lowest observed activity varies from core to core. This methodology is consistent with previously published papers using alpha spectrometric techniques to estimate 210Pb systematics and SARs in sedimentary systems (e.g., Brossier et al, 2014;Chambers et al, 2017;Galka et al, 2017;Greiner et al, 2013, Kolker et al 2009Wachnicka et al, 2013). based on the inventories, it is possible to calculate directly age of each layer, and then to estimate SAR and MAR, such values would have been interesting to discuss also (temporal trends, potential change in accretion regarding sea level rise).…”
supporting
confidence: 82%
“…High and low marsh zones were delineated by eye using differences in vegetation color on Google Satellite base map imagery (Figure 4 and Figure A5). The halophyte-dominated low-marsh plant assemblage was a lighter shade of green compared to the darker green of the high marsh plant assemblages (Chastain 2017). Additionally, high and low marsh zones were identified using vegetation surveys at 176 sample points (22 sediment core sites and 154 additional sample sites).…”
Section: Marsh Area and Volumementioning
confidence: 99%